MODERN APPROACHES TO EARLY DETECTION AND PREVENTION OF REFRACTIVE ERRORS IN PRESCHOOL CHILDREN (E Global Congress, 2025)
Refractive errors are among the most common visual impairments in preschool children, affecting their cognitive and social development. Early detection and prevention strategies play a crucial role in mitigating long-term visual complications. Modern approaches to managing refractive errors include advanced screening techniques, digital diagnostic tools, and innovative therapeutic interventions. The integration of automated refractometry, photorefraction, and artificial intelligence-based screening methods has improved the accuracy and efficiency of early diagnosis. Preventive measures such as outdoor activities, controlled screen exposure, and visual hygiene education have proven effective in reducing the incidence of myopia and other refractive errors. This study explores the latest advancements in early detection and prevention of refractive errors in preschool children, emphasizing the importance of a multidisciplinary approach involving pediatricians, ophthalmologists, and educators. By implementing evidence-based strategies, healthcare systems can significantly reduce the burden of childhood visual impairments and improve children's overall quality of life.